2006
DOI: 10.1021/bi0601813
|View full text |Cite
|
Sign up to set email alerts
|

Structures of the Dimeric and Monomeric Variants of Magainin Antimicrobial Peptides (MSI-78 and MSI-594) in Micelles and Bilayers, Determined by NMR Spectroscopy

Abstract: Magainins are antimicrobial peptides that selectively disrupt bacterial cell membranes. In an effort to determine the propensity for oligomerization of specific highly active magainin analogues in membrane mimetic systems, we studied the structures and lipid interactions of two synthetic variants of magainins (MSI-78 and MSI-594) originally designed by Genaera Corp. Using NMR experiments on these peptides solubilized in dodecylphosphocholine (DPC) micelles, we found that the first analogue, MSI-78, forms an an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
159
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 160 publications
(172 citation statements)
references
References 41 publications
13
159
0
Order By: Relevance
“…In our hands, higher order AMPs also tend to be more cytotoxic, reflecting their increased interactions with mammalian membranes. B2088 retains its monomeric state in various media, which is in agreement with biophysical observations of other AMPs (51,63,79). The trend in designing AMPs toward higher covalent order might be limited by increased cytotoxicity and can be counteracted by designing lower order AMPs, maintaining high mobility in LPS and providing higher concentrations at the lipid surfaces of bacteria.…”
Section: Discussionsupporting
confidence: 87%
“…In our hands, higher order AMPs also tend to be more cytotoxic, reflecting their increased interactions with mammalian membranes. B2088 retains its monomeric state in various media, which is in agreement with biophysical observations of other AMPs (51,63,79). The trend in designing AMPs toward higher covalent order might be limited by increased cytotoxicity and can be counteracted by designing lower order AMPs, maintaining high mobility in LPS and providing higher concentrations at the lipid surfaces of bacteria.…”
Section: Discussionsupporting
confidence: 87%
“…For MSI-78, dimerization screens the hydrophobic residues reducing the affinity for mammalian membranes which contain zwitterionic lipids in the outer leaflet, while exposing positive charges. MSI-78 propensity to form stable dimers make it more selective and active toward the negatively charged bacterial membranes if compared to MSI-594 [39]. Examples of AMPs, other than magainins, that are proposed to form this type of pore include mellitin and LL-37 [56,[64][65][66].…”
Section: Permeabilization Mechanismsmentioning
confidence: 99%
“…In particular, Ramamoorthy et al used specific membrane model systems and nuclear magnetic resonance (NMR) to characterize structure and dynamics of several AMPs such as pardaxins [36][37][38], MSI-78 (Pexiganan) and MSI-594 synthetic magainin analogues [39,40], MSI-843 lipopeptide [41], granulysin [42], tachyplesin [43] and a cyclic peptide subtilosin A [44]. In particular, the studies on pardaxin [36,38] have shown the role of cholesterol on inhibiting the membrane disruption and the role of the peptide on the formation of cholesterol-rich domains.…”
mentioning
confidence: 99%
“…Among them, the cyclopeptide colistin (polymyxin E) (6-9) is currently used in the clinic for multiresistant infections, while other families, like cationic steroids (ceragenins [10,11] or cationic antimicrobial peptides [e.g., magainin, dermaseptin, cecropin] [12][13][14]) and peptidomimetic compounds (e.g., MSI-78, MSI-594) (15), have also been identified to be antimicrobial agents with potent activity against P. aeruginosa. Due to their mode of action, which implies the formation of pores in the bacterial membranes (16,17), in vitro resistance to these cationic amphiphiles is rarely observed.…”
mentioning
confidence: 99%